Estrategia lúdica "CARITAS FELICES" para Desarrollar el aprendizaje significativo en Niños(as) de 04 años de la Institución Educativa Inicial Nº 288 provincia de Rioja - Pacheco Alvarado, Diana María (2007)
The present investigation is an experimental level dealing with boys and girls from the "Ana Sofia Guillena Arana" 288 kindergarten Rioja city - San Martin Region. The general goal of investigation was to propouse apply the Strategy Happy Faces to develop the significative learning with kids four years old. Playing is the base of intensive it is a most in a young child life that will better develop his future. The activities were based and young child early life and theory was influence based in Piaget, Vigotsky, and Ausubel, the reason for this it's because this theory considers playing an important part of a young child life. The Sample was made of 52 kids; of wich 26 were from rabbits section (experimental group) and 26 from chicks section (controul group) previously a pre test was conducted. To obtain relevant resoults. The lucidia Strategy was apply on the experimental group. Later the pre test was conducted to confirm our resoults. The resoults allow was to except the alternative high hypothesis wich chisquare value is 24.04 and the critical value is 3.84 with 5% level significance. This indicate the lucidia Strategy Happy Faces has developed the significative learning of kids tour years old. Our study found the kids in experimental group had grader learning in the post test than kids in the control group did with their post test. Meaning the lucidia Strategy has produce significant resoults in the learning of boys and girls tour years old in Ana Sofia Guillena Arana 288 Kindergarten Rioja city. The application Happy Faces has produce significant resoults in young kids, this method should be use to better educative system of our country. New methods should also be explored that can better our educative system.